2017
DOI: 10.12693/aphyspola.131.819
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties and Structure of Non-Oriented Electrical Steel Sheets after Different Shape Processing

Abstract: Non-oriented electrical steel sheets are the most often used materials in electrical rotary machines. Raw sheets must be formatted by various methods, e.g., punching, laser, spark or water stream cutting. Basic parameters of magnetic, electrical, and mechanical properties of the sheets are usually obtained from the producer, but namely magnetic properties are changed in dependence on additional machining processes. The aim of this study is to describe changes in magnetic properties after punching, laser or spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
(4 reference statements)
1
0
0
Order By: Relevance
“…In contrast, laser cutting does not induce any changes in the grain morphology near the cut line. Similar observations about punching and spark erosion can be found in [32,35,56,58,59]. Comparing the results of the above studies, it was found that punching "generates" plastic deformations much smaller than cutting with a guillotine.…”
Section: Morphology Of Grains and Measurements Of The Macroscopic Pro...supporting
confidence: 78%
“…In contrast, laser cutting does not induce any changes in the grain morphology near the cut line. Similar observations about punching and spark erosion can be found in [32,35,56,58,59]. Comparing the results of the above studies, it was found that punching "generates" plastic deformations much smaller than cutting with a guillotine.…”
Section: Morphology Of Grains and Measurements Of The Macroscopic Pro...supporting
confidence: 78%